Проблеми та перспективи розвитку подієвого туризму в Україні (Economics and region, 2024)
The article examines the recovery of the event tourism market in Ukraine following the full-scale invasion of Russian troops in 2022, focusing on organizing cultural and social events during the war. Key factors influencing market development are identified, including the preservation of cultural identity, the cohesion of citizens, and the support of the population's morale. The importance of cultural events in sustaining national resilience and psycho-emotional rehabilitation is explored, as well as the role of international solidarity in promoting Ukraine globally. The concept of festival recovery is proposed as part of a strategy to preserve cultural unity. The significance of cultural initiatives for maintaining moral resilience, both domestically and internationally, is emphasized. Examples of the recovery of significant festivals in Ukraine, which have become symbols of resilience and cultural revival even in wartime, are examined. The article also explores the specific conditions under which cultural events are held in Ukraine during the war. Attention is given to ensuring the safety of participants and visitors, as well as to communication aspects of organizing events in uncertain conditions. The use of digital technologies for online and hybrid events, allowing broad audience engagement and maintaining cultural unity beyond Ukraine's borders, is also discussed. An important part of the research is the analysis of problems hindering the development of event tourism in Ukraine, such as the lack of proper infrastructure, insufficient strategic planning, and lack of investment. Despite significant opportunities, such as cultural and natural resources, economic instability and the ongoing war remain the main obstacles to realizing the potential of the event tourism market. Ways to overcome these problems are proposed, including the integration of international standards in event organization, attracting investment for infrastructure development, and actively using digital platforms to support communication with the audience.
Keywords: event tourism; cultural events; recovery; cultural identity; digital technologies; online international events; safety; strategic planning